The Effectiveness of Social Stories Implemented Through Technology: Is There a Difference in Outcomes between Males and Females? - Padilla, Denice Mena; Pierson, Melinda R. (Wydawnictwo Naukowe UAM, 2015)
The effectiveness of technologically-based social stories for males and females with autism is explored. An increase in positive behavior responses and improved communication are two outcomes compared to paper-based social stories. Additional research should continue to validate the use of technology supports for males and females with disabilities in the classroom.
Keywords: social stories; technology; males; females